1993
DOI: 10.1002/ana.410340311
|View full text |Cite
|
Sign up to set email alerts
|

Differential neural activity in the human temporal lobe evoked by faces of family members and friends

Abstract: In 6 patients, depth electrodes revealed differential evoked responses to familiar versus novel faces. These differential responses were obtained in the amygdala, hippocampus, and temporal neocortex but not in the dorsolateral frontal or cingulate cortex. The limbic and temporal structures that differentiated novel from familiar faces did not respond differentially to variations in luminance. Limbic structures and temporal cortex thus appear to participate in face recognition and in encoding the familiarity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…This response at 170 ms is not influenced by the familiarity of the face (Bentin et al, 1996;Bentin & Deouell, 2000;Eimer, 2000a), thus presumably corresponding to bottom-up aspects of perceptual processing (akin to early structural encoding in the model by Bruce & Young, 1986). Postperceptual processing of faces, such as recognition of identity, relies on anterior temporal cortices and occurs with latencies in excess of 200 ms (Seeck et al, 1993). Later activity in occipital regions that discriminates between different emotions is also seen after 500 ms and is influenced by the particular task, presumably reflecting top-down modulation (Krolak-Salmon, Fischer, Vighetto, & Mauguiere, 2001).…”
Section: Process Considerationsmentioning
confidence: 88%
“…This response at 170 ms is not influenced by the familiarity of the face (Bentin et al, 1996;Bentin & Deouell, 2000;Eimer, 2000a), thus presumably corresponding to bottom-up aspects of perceptual processing (akin to early structural encoding in the model by Bruce & Young, 1986). Postperceptual processing of faces, such as recognition of identity, relies on anterior temporal cortices and occurs with latencies in excess of 200 ms (Seeck et al, 1993). Later activity in occipital regions that discriminates between different emotions is also seen after 500 ms and is influenced by the particular task, presumably reflecting top-down modulation (Krolak-Salmon, Fischer, Vighetto, & Mauguiere, 2001).…”
Section: Process Considerationsmentioning
confidence: 88%
“…The subjects found the task difficult, so the performance showed considerable intersubject variability. On average, the subjects performed at chance level although they accomplished almost perfectly a simpler face-matching task (35).…”
Section: Implicit Memory Of Facesmentioning
confidence: 94%
“…To investigate this type of face recognition, photographs of family members and close friends, as well as unknown faces with similar facial expressions, were presented to patients with epilepsy who had depth electrodes in the frontal and temporal lobes (35).…”
Section: Recognition Of Highly Familiar Faces Personally Known By Thementioning
confidence: 99%
“…The intracranial recordings from the face-specific sites [10] did not show significant differences for components P150, N200, P290, P350, or N700 between famous and nonfamiliar faces. On the other hand, intracranial recordings by the other authors [11] showed differential responses, mainly from the right amygdala, starting from about 150 ms. The purpose of the current study was to determine the timing and possible scalp locations for the differences in face processing related to face familiarity.…”
Section: Introductionmentioning
confidence: 95%